USING NURSERY RHYME TO TEACH LISTENING SKILL - Ade Irma Suryani; Fitri Novia (Language and Education Journal, 2017)
Listening is a process to construct the meaning between speaker and listener. Unfortunately, in listening students not only have the important things but also difficult things. There are many kinds of song that teacher can use in teaching listening to support their teaching process. One of a song is a nursery rhyme. Hence, the purpose of this study was to find out whether or not there was a significant difference in listening achievement between students who were taught by using nursery rhymes and who were not. In conducting this study, quasi experimental design was used. In this study, the writer took the sample by using purposive sampling method. The writer used a written test in the form of fill in the blank. The t-test was used to analyze the data. Based on the result of the independent t-test, the t-obtained was 2.022. At the significance level of p<0.05 and the degree of freedom (df) 68. The critical value of ttable was 1.9955. Since the value of t-obtained (2.022) was higher than the value of t-table (1.9955) and p-value (0.047) was lower than ά-value (0.05), the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. In the other words, there was a significant difference in students’ listening achievement between students who were taught by using nursery rhyme and that of those who were not